Rituximab therapy in steroid-resistant severe hypothyroid Grave′s ophthalmopathy - Aditi Pandit; Abhay Gundgurthi; Sandeep Kharb; Karninder S Brar; M K Garg (Indian Journal of Endocrinology and Metabolism, 2013)
Association of Grave′s ophthalmopathy with hyperthyroidism is well known, and it has also been reported in euthyroid or hypothyroid autoimmune thyroiditis, which rarely requires treatment. Here, we report a case of bilaterally symmetrical severe corticosteroid-resistant hypothyroid Grave′s ophthalmopathy successfully treated with rituximab.